2017
DOI: 10.33549/physiolres.933579
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models in the Research of Abdominal Aortic Aneurysms Development

Abstract: Abdominal aortic aneurysm (AAA) is a prevalent and potentially life threatening disease. Many animal models have been developed to simulate the natural history of the disease or test preclinical endovascular devices and surgical procedures. The aim of this review is to describe different methods of AAA induction in animal models and report on the effectiveness of the methods described in inducing an analogue of a human AAA. The PubMed database was searched for publications with titles containing the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 90 publications
(73 reference statements)
0
86
0
1
Order By: Relevance
“…The limitations of our study require consideration. Several animal models of AAA have been developed in mice including injury of the aortic wall with calcium chloride or elastase (Patelis et al, 2017). Compared with other models, the AngII-infused model supports an imbalance of the renin-angiotensin system in the pathogenesis of AAA (Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The limitations of our study require consideration. Several animal models of AAA have been developed in mice including injury of the aortic wall with calcium chloride or elastase (Patelis et al, 2017). Compared with other models, the AngII-infused model supports an imbalance of the renin-angiotensin system in the pathogenesis of AAA (Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Differences between species and individuals perhaps lead to diverse consequences. For example, unlike humans, mice often present suprarenal AAAs and their relevance remains somewhat limited by their inability to expand indefinitely with time (Patelis et al, 2017). So further experiments might be needed to evaluate the effect of BAZ in human AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic dilatation in CaCI 2 model increases with time and it is caused by progressive infiltration of mast cells and T lymphocyte to adventitia layer. Vascular smooth muscle cells disappear due to calcification and fragmentation in elastic fibers and they are replaced by neutrophils [27]. Most important aneurysm formation mechanisms of CaCI 2 application are medial degeneration and leucocyte infiltration.…”
Section: Calcium Chloride Modelmentioning
confidence: 99%
“…In some studies, it was shown that hemodynamic stress facilitates AAA predisposition and flow alterations significantly affect arterial lumen diameter. Also, poststenotic dilatation was detected at the area of oscillatory shear stress distal to the cast in some studies [27].…”
mentioning
confidence: 98%
“…Abdominal aortic aneurysm (AAA) is characterized by chronic remodeling of aortic wall tissue, however, its pathogenesis remains poorly understood. [ 1 ] Animal models have been developed to mimic human AAA disease, [ 2 ] which included genetically predisposed AAA model, chemical injury AAA model, and hemodynamically-induced AAA model. Although the chemical injury AAA model has been popular used in animal studies, [ 3 9 ] this model does not always induce stable AAA.…”
Section: Introductionmentioning
confidence: 99%